2009
DOI: 10.3329/taj.v22i2.37718
|View full text |Cite
|
Sign up to set email alerts
|

Findings of the 3-Month Supportive Treatment with Oncoxin Solution Beside the Standard Modalities of Patients with Different Neoplastic Diseases.

Abstract: The incidence of Cancer is still increasing worldwide, specially, at an alarming rate in the developing countries and remain one of the major cause of morality worldwide. The role of different antioxidants, both in fruits and vegetable and in synthetic form as chemo-preventive measure is now well established from different studies. The incidence of cancer is lower in those countries where the traditional diet provides plenty of antioxidants. The aim of this study is to evaluate standard modalities of patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…Interestingly, 26% of Ocoxin supplemented patients lived for another 3 months, while 21% of Ocoxin having individuals prolonged their life for 9 months 61 . This observation goes in line with that reported by Uddin et al (2018) , observing increased survival rates in Ocoxin receiving patients from head and neck, breast and uterine cervix cancer compared to control group (87,65% vs 74,68%, respectively) 31 , always under CT routine. In line with these findings, clinical trials using Melatonin as adjuvant to CT resulted in 1 year increased survival rate while promoting the regression of tumors 62 .…”
Section: Ocoxin Increases Patient Survivalsupporting
confidence: 92%
See 3 more Smart Citations
“…Interestingly, 26% of Ocoxin supplemented patients lived for another 3 months, while 21% of Ocoxin having individuals prolonged their life for 9 months 61 . This observation goes in line with that reported by Uddin et al (2018) , observing increased survival rates in Ocoxin receiving patients from head and neck, breast and uterine cervix cancer compared to control group (87,65% vs 74,68%, respectively) 31 , always under CT routine. In line with these findings, clinical trials using Melatonin as adjuvant to CT resulted in 1 year increased survival rate while promoting the regression of tumors 62 .…”
Section: Ocoxin Increases Patient Survivalsupporting
confidence: 92%
“…Petients with higher Karnofsky index show better prognosis. It is to note that Ocoxin administration along with CT resulted in 59,26% increase in Karnofsky index compared to 30,38 reported in patients receiving CT alone, suffering from different neoplasic diseases, such as head and neck, breast and uterine cervix cancer [31]. In concordance, other natural compounds have shown efficacy when using as adjuvant along with CT regimens, increasing the Karnofsky index in cancer patients, such as those suffering from Non Small Cell Lung Cancer (NSCLC) [44].…”
Section: Ocoxin and Karnofsky Indexmentioning
confidence: 80%
See 2 more Smart Citations
“…In a Japanese clinical study carried out in terminal stage patients of hepatocellular carcinoma, it was observed that 21% of patients were alive at the end of the treatment in the treatment group, whereas in the control group they were dead (79). Another clinical study in Bangladesh demonstrated more tolerance to cancer treatment, which was found to improve patient survival and quality of life (80). A clinical study of pancreatic cancer proved that OV reduced the stromal-mediated chemoresistance (81).…”
Section: Discussionmentioning
confidence: 99%